Intensification of Back Muscle Strength Testing in Physical Education of Students by Applying Information and Communication Technologies - Oksana Blavt; Zinoviy Mykytyuk; Yaroslav Hnatchuk; Oleh Stechkevych; Tetiana Helzhynska (OVS LLC, 2022)
The purpose of this study is the experimental substantiation of the implementation of information and communication technologies to test the control of back muscle strength in the process of physical education of students.  Materials and methods. General scientific methods were used to solve the research problems: analysis, synthesis, generalization, induction and systematization, technical modeling, pedagogical experiment, pedagogical testing, and mathematical methods. The study involved 240 students aged 17 to 18 at the beginning of the study.  Results. An electronic device for determining the strength of the muscles of the back was developed and tested, the readings of which allow the user to get clear current information on the panel of a personal computer. The device was built on a combination of modern electronic technologies and software. For the purposes of the experimental substantiation of the developed back muscle strength control device, a correlation analysis was used to empirically investigate the authenticity degree of the tests used to control back muscle strength. According to the results of the reliability of the tests of back muscle strength control tests, the results of which were recorded using a dynamometer, those are between low and medium. The recording of the back muscle strength test results with the developed device ensured the achievement of a high level of test authenticity.  Conclusions. The result of the research study aimed at solving the problematic aspects of test control was to ensure the appropriate degree of authenticity of the tests used to control back muscle strength. The recording of the back muscle strength test results with the developed device ensured the achievement of a high level of test authenticity.